Increasing adult ICU nurse's bioethical knowledge on death and dying - Olguera, Ana Macapanas (2000)
Death education programs for health professionals, whose work involves "the laying of hands" and making decisions of a life-death nature, is more intricate than any other death education programs. Ideally, death education programs intended for nurses and physicians must be build upon a sound basic education on death and dying and more importantly, strong bioethical principles which would guide healthcare professionals in making sound bioethical decisions.In this light, this study was conducted to determine the cognitive level of ICU nurses on care of death and dying patients before and after instituting bioethical teaching program related on this topic and to ascertain the relationship of the following variables (age, civil status, length of service and personal experience of death) with the nurses' bioethical knowledge on care of death and dying patients.The study utilized quasi-experimental design specifically pretest-posttest model. It was conducted in two adult Intensive Care Units namely Medical ICU and Central ICU. Thirty-three nurses who have met the set inclusion criteria were included in this study.A 30-item questionnaire was given to all nurse participants. The questionnaire included our hypothetical cases that described clinical situations that needed decisions to presented bioethical dilemma. Questions involved the entire major groups of bioethical principles namely maximize good, respect for person and justice. The said questionnaire was given twice. Pretest was given initially and then after two weeks, bioethical teaching program was given. After another two weeks, the same set of questionnaire was given again as posttest.
Respondents were also requested to fill out the information sheet provided in order to obtain the sociodemographic data and length of service rendered by each nurse.The results of the study showed an increase in the cognitive level of respondents when they were exposed to structured bioethical teaching program. The posttest scores ranged from 16 to 25 with a mean of 21.03 and a standard deviation of 2.53, versus the pretest scores, which ranged from 5 to 25 with a mean of 19.27 and a standard deviation of 3.98.To determine the significant relationship between the given variables namely age, civil status, length of service and personal experience of death with the difference of both scores. Pearson Product Moment Correlation was used. This test showed that the above variables namely age (r = -.068); civil status (r = 0.12799), length of service (r= 0.101) and personal experience of death (r = 0.027267) have a very little, (if any) correlation on the bioethical knowledge of ICU nurses included in the study. Hence, the younger the nurses, the higher the scores obtained in the given questionnaire related to bioethical principles. In addition, the shorter the length, the shorter the length of service rendered in the hospital, the more appropriate bioethical decisions being made as evidenced by the higher scores obtained. Based on the scores, it has been noted that the single respondents can make more appropriate bioethical decisions as compared with their married counterparts. Personal experience of death, on the other hand, does not guarantee sound bioethical decisions as seen from the posttest scores of the nurse respondents.To establish the significant difference between pretest and posttest scores, t-test for dependent (paired) samples was utilized and the level of significance was set at .05. as previously mentioned, the study showed an increase in the cognitive level of ICU nurses when they were exposed to structured bioethical teaching program.Based on these findings, it is recommended that nurses and those involved in caring for dying patients must continue to provide not only the essentials of basic bedside nursing but also continue to promote comfort measures when resuscitation and other medical/technical management had failed. Such corresponding needs of dying patients can only be answered when nurses continuously update themselves on various issues related to bioethical dilemmas where respect, beneficence and nonmaleficence are practiced.It also hoped that the results of this study would serve as a basis for nursing administrators to pursue regular bioethical seminars and other related workshops. Such seminars could address the needs of nurses particularly those who belong to older and senior group who need more information in making sound bioethical decisions. More over, it is also hope that this study would serve as a guide for hospital administrators in developing specific policies on various bioethical dilemmas encountered by the health team when caring for dying patients.
Thesis (Master of Arts in Nursing)--University of the Philipines Manila.
Keywords: Death and dying; Bioethics